Cultural change and industrial heritage tourism: material heritage of the industries of food and beverage in Catalonia (Spain). Issue 3 (27th May 2017) - Prat Forga, José Maria; Cànoves Valiente, Gemma
Abstract : Tourism is recognised as an agent of social and cultural change and has been identified as a force for both cultural enrichment and rejuvenation of territories. This article analyses the historical evolution and the opportunities that a type of the industrial heritage, the old industry of food and beverage, presents as tourist resource, both its products and processes and its architectural structure. There are numerous examples in all developed countries; however, in this work is analysed the case of Catalonia (Spain), where museums and interpretation centres have been created in abandoned factories, and these old factories have increasingly become a new attraction for those tourists interested to know more about the industrial past. This new tourism has an important geographic content since it recovers the cultural, social and economic values of the old industrial landscapes. This article's first goal is to review the historical evolution of the industry of food and beverage in Catalonia in the last centuries, creating a material heritage that in this new millennium, in which rapid changes and transformations are taking place, has been converted into tourist products. Second, to analyse the feasibility of this tourism with these attributes: potential, stakeholders, adaptive reuse, economics, authenticity and perceptions.